2022
DOI: 10.1039/d2fo00560c
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of psyllium on the prevention and treatment of cardiometabolic diseases

Abstract: Cardiometabolic diseases are reaching epidemic proportions worldwide. Nevertheless, current therapeutic strategies are insufficient; thus, studying novel complementary and alternative medicines remains of the upmost importance. Psyllium has been used for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…Yamagishi et al (2023) reported that cellulose can mitigate neurodegeneration-related nerve inflammation and decrease the accumulation of βAP in the brain through intestinal bacteria which synthesize butter acid (as a result of dietary fiber fermentation, short-chain fatty acids, and phytosterols). McRorie (2015), Shah et al (2020) and Chen et al (2022) explain the improvement of neurometabolism by the unique viscous potential of Plantago psyllium, which refines the gut microbiome, has antibacterial properties and reduces the levels of cholesterol and glucose in the blood. However, Hansan et al (2017) believe that cellulose might stimulate neurometabolism by stimulating the function of the immune system, decreasing insulin resistance, enhancing glucose metabolism, and regulating the activity of erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Yamagishi et al (2023) reported that cellulose can mitigate neurodegeneration-related nerve inflammation and decrease the accumulation of βAP in the brain through intestinal bacteria which synthesize butter acid (as a result of dietary fiber fermentation, short-chain fatty acids, and phytosterols). McRorie (2015), Shah et al (2020) and Chen et al (2022) explain the improvement of neurometabolism by the unique viscous potential of Plantago psyllium, which refines the gut microbiome, has antibacterial properties and reduces the levels of cholesterol and glucose in the blood. However, Hansan et al (2017) believe that cellulose might stimulate neurometabolism by stimulating the function of the immune system, decreasing insulin resistance, enhancing glucose metabolism, and regulating the activity of erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation may be that dietary fibre naturally increases the feeling of satiety, consequently reducing the overall caloric intake [ 37 ]. The observed effects caused by inulin or psyllium may be related to the fact that both forms dissolve well in water, forming a gel in the small intestine, which prolongs the feeling of satiety, thus reducing the intake of energy and weight loss, or to the specific rheological properties of high-fibre foods that require longer chewing [ 40 ]. Adam et al [ 37 ] prove that soluble dietary fibre of a prebiotic nature stimulates the secretion of satiety hormones, such as glucagon-like peptide-1 (GLP-1) and tyrosine-tyrosine peptide (PYY), by the mucosa of the small intestine, which effectively suppresses appetite and reduces the food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects include gastrointestinal discomfort, mild anaphylactic allergic reactions, bowel obstructions, and esophageal obstructions [16,22,64]. Increased water consumption reduces obstructions [164].…”
Section: Psylliummentioning
confidence: 99%